POLYMER DISPERSED LIQUID CRYSTAL GRATINGS’ EVOLUTION AND INVESTIGATION OF THEIR DIFFRACTION EFFICIENCY - Galstyan, A. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
In this paper evolution of thick anisotropic gratings formation in photomonomer–liquid crystal mixture is modeled. The polymer and monomer concentra-tions’ distributions are obtained from modeling of grating formation process. Distributions of dielectric permittivities from Lorentz-Lorenz and more simple approximate formulas are obtained. The comparison of received distributions and appropriate diffraction efficiencies for s- and p-polarized probe beams are done. It appears, that diffraction efficiencies calculated by exact and approximate distributions qualitatively coincide, however there is a quantitative difference and it depends on polarization of the probe beam.